IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN TEMATIK DI KELAS VI SDN 033 ASMI KOTA BANDUNG - Nurfaidah, Siti Sholiha; Lukman Praja, Azis; Fazriyah, Nurul; Mamad, Akhmad (STKIP Subang, 2019)
Changes in the context of education are always made in order to improve the quality of education output. One learning model that can be applied is thematic learning with a scientific approach. A scientific approach is a learning process that uses a scientific thought process. Where learning is very important for students to find and build their own knowledge that is fun and meaningful. The purpose of this research is to get a picture of the implementation of a scientific approach in thematic learning in class VI SDN 033 Asmi Bandung. This research is a descriptive research. The research subjects in this study were model teachers (lecturers who teach in schools) and class VI A students at SDN 033 Asmi. Data collection tools in this study are interview guidelines, observation sheets and study documentation. Data analysis was performed by data reduction, data display and conclusion drawing. The results showed that the model teacher had implemented learning using a scientific approach which was carried out through the steps of the activity: 1) observing, 2) asking questions, 3) trying, 4) associating, and 5) communicating. Each step has been implemented well but not always done sequentially on every learning that is done. Thematic learning with a scientific approach has made the learning process more active and enjoyable. So that students really become the center of activity in the learning process that takes place.